Modular colorings of join of two special graphs - N Paramaguru; R Sampathkumar (Electronic Journal of Graph Theory and Applications (EJGTA), 2014)
For k≥2, a modular k-coloring of a graph G without isolated vertices is a coloring of the vertices of G with the elements in Zk having the property that for every two adjacent vertices of G, the sums of the colors of their neighbors are different in Zk. The minimum k for which G has a modular k-coloring is the modular chromatic number of G. In this paper, we determine the modular chromatic number of join of two special graphs.